In vitro induction of Î±-pinene, pulegone, menthol, menthone and limonene in cell suspension culture of pennyroyal (Mentha pulegium) - Darvishi, E; Kahrizi, D; Bahraminejad, S; Mansouri, M (Cellular and Molecular Biology, 2016)
Medicinal plants are known as important sources of secondary metabolites. Because of the economic value of pennyroyal [Mentha pulegium L. (Lamiaceae)] in food industries, propagation of this valuable plant has special importance. Plant cell suspension culture can increase some produced components. The aim of this research was performing cell culture for induction of some secondary metabolites of M. pulegium and compares it with native one. The MS medium was used for suspension culture. To investigate quantitative materials, 4 levels of yeast extract elicitor (20, 40, 60 and 80 mg/L) and salicylic acid in 4 levels (2, 4, 6 and 8 mg/L) were used. Obtained extracts were analyzed by GC-MS. Statistical analysis showed that the amount of limonene, menthone, menthol and Î±-pinene were more than mentioned compounds in natural plant as control. The maximum amount of this metabolites were obtained as limonene (in 60 mg/l yeast extract), menthone (in 40 mg/l yeast extract and 2 mg/l salicylic acid), menthol (in 6 mg/l salicylic acid) and Î±-pinene (in 4 mg/l salicylic acid) in the M. pulegium cell culture. The Pulegone was fond more in natural plants than cell culture mass. The most important secondary metabolites were increased by cell culture containing of salicylic acid and yeast extract elicitors in M. pulegume.